Mathematical modelling of convection and macrosegregation during casting of metallic alloys. (20th January 2011) - Singh, A.K.; Basu, B.; Ghosh, A.
Macrosegregation of solute is one of the important casting defects and is present in both continuous cast products and ingots. It results from the movement of segregated solid or liquid over macroscopic distances during the progress of alloy solidification. Macrosegregation is governed by a large number of interacting phenomena such as heat transfer, fluid flow, species transport, phase change, morphological transition, etc., which, in turn, are dependent on process and design parameters such as geometry of the casting strand, casting speed, super heat, cooling rate, composition of the melt, parameters controlling forced convection and so on. It is important to understand the role of various parameters on the evolution of macrosegregation. The modelling of solidification phenomena in general and transport phenomena-based alloy solidification in particular have received considerable attention in the past few decades. These models have allowed greater understanding of the coupled nature of the process and have made it possible to devise ways for the control of macrosegregation. The present author and his co-workers have done extensive laboratory experiments and mathematical modelling on macrosegregation in alloys. The paper briefly outlines these. It also discusses some special fundamental features of macrosegregation in continuous casting of steel.